84.0k views
2 votes
Solve for b.
-7b – 12 = -61

1 Answer

4 votes


\huge\text{Hey there!}


\mathsf{-7b - 12 = -61}


\large\textsf{ADD 12 to BOTH SIDES}


\mathsf{-7b - 12 + 12 = -61 + 12}


\large\textsf{CANCEL out: -12 + 12 because that gives you 0}


\large\textsf{KEEP: -61 + 12 because it helps solve for your b-value}


\mathsf{-61+12=\bf -49}


\large\text{NEW EQUATION: \textsf{-7b = -49}}


\large\textsf{DIVIDE -7 to BOTH SIDES}


\mathsf{(-7b)/(-7)=(-49)/(-7)}


\large\textsf{CANCEL out: }\mathsf{(-7)/(7)}\large\textsf{ because that gives you 1}


\large\textsf{KEEP: }\mathsf{(-49)/(-7)}\large\textsf{ because that gives you your b-value}


\mathsf{(-49)/(-7)= \bf b}


\uparrow\large\text{SIMPLIFY ABOVE \& YOU HAVE YOUR ANSWER}\uparrow


\mathsf{-49/ -7= \bf 7}


\boxed{\boxed{\large\text{Answer: \huge \bf b = 7}}}\huge\checkmark


\large\text{Good luck on your assignment and enjoy your day!}

~
\frak{Amphitrite1040:)}

User AStewartDesign
by
6.7k points